ANALISIS BIAYA IMBANGAN DAN POTENSI PENDAPATAN USAHATANI PADI DI KECAMATAN PUNGGUR KABUPATEN LAMPUNG TENGAH - Tri Agustam; Bustanul Arifin; Lina Marlina (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2016)
This research aims to analyze the opportunity cost of paddy farmer, the income potencials of paddy farming and factors affecting the income of paddy farmers. This study was a survey method conducted in Astomulyo Village, Punggur Sub-District, Lampung Tengah Regency in November 2015 - January 2016. This location was selected purposively as Astomulyo Village is one of the paddy and pineapple producers. The number of samples was 42 respondents selected by using Simple Random Sampling. The opportunity cost was analyzed by comparing paddy farming and other farmers’ ocupationsusing two paired sample t-test. The potential income of paddy farming was calculated on paddy farming income and opportunity cost and analyzed using two paired sample t-test, The factors are paddy farming income using Cobb Douglass function profit. This research results showed that farmers opportunity cost was Rp17,275,316.00, meaning that the opportunity cost  of farmers was higher than the income of paddy farming. The income potencyof paddy farming was Rp14,246,328.00, implying that the opportunity cost affected the incrase of paddy farmers’ income. The factors affecting the paddy farming income were land size, seed cost, dan workers’ wage.Keywords : income, opportunity cost, paddy farmers, the factor affected to income